Cimicifuga racemosa: uma nova perspectiva para o tratamento de distúrbios neurológicos. - Frota, Annyta Fernandes (2015)
Aplause’s phytotherapic is a compound derived from ethanolic extract of the plant rhizome Cimifuga racemosa (Cr), commercially used for treatment of symptoms occurring at menopause. Cr shows as the main bioactives predominant the phytoestrogens. Despite reports in the literature indicate others activities with pharmacological potential, the effects of the chronic administration of this phytotherapic on the Central Neurvous System (CNS) remain uncleair. Thus, the present study investigated the possible neuropsychopharmacologic effects and a potential neuroprotective activity of Cr by in vivo and in vitro models. For this study, we used the ethanolic extract isolated from Cr present in the Aplause’s phytotherapic. Initially, male Swiss mice (25-30 g) were chronically treated with Cr (1; 5; 10; 25; 50; 100 e 200 mg/Kg/21 days/ per os) or Saline (0.9%). After, animals were submitted to neuropsychopharmacological preliminary evaluation and possible physiological alterations, following by locomotor, anxiolytic, anti-depressive and hypnotic/sedative assays, respectively. To investigate the potential neuroprotective action, Wistar rats (250-300 g) were submitted to Parkinson’s disease model (PD) induced by unilateral injection of 6-hydroxydopamine (6-OHDA) on striatum, following by treatment with Cr (1.25; 2.5 e 5 mg/Kg/ 21 days/ per os) or Saline (0.9%). At 21st day, rats were submitted to neurobehavioral assays (Open field test, Rota rod and apomorphine-induced rotational test). Then, animals were euthanized and cerebral areas were dissected and used to perform neurochemical and transcriptional analyses. In addition, to evaluate a possible antioxidant activity in vitro, we performed assays to determine the effect of Cr (50, 100 and 200 µg/mL) on structural and electro-chemical alterations induced by pro-oxidant agents in mitochondria. Our results shows that the treatment with Cr promotes anxiolotyc and sedative effects in mice, modulation and transcriptional changes on hippocampus like Imipramine. Cr shows neuroprotective activity against neurobehavioral, neurochemical and transcriptional alterations induced by 6-OHDA into striatum from rats. Cr exhibited antioxidant activity in vivo and in vitro models used in this study, which can be associated with neuroprotective effects observed in vivo. Additionally, Cr shows pharmacologic safety in animal models. Therefore, Cr represents a phytotherapic with possible neuropsychopharmacologic implications and as a potential therapeutic strategy against neurodegenerative disorders.